Static and Dynamic Electronic (Hyper)polarizabilities of Dimethylnaphthalene Isomers: Characterization of Spatial Contributions by Density Analysis. (28th October 2013) - Alparone, Andrea
Abstract : Static and frequency-dependent electronic (hyper)polarizabilities of the dimethylnaphthalene (DMN) isomers were computed in vacuum using the Coulomb-attenuating Density Functional Theory method. The nonlinear optical Second Harmonic Generation (SHG) and Electro-Optical Pockels Effect (EOPE) were investigated at the characteristic Nd:YAG laser wavelength of 1064 nm. The response electric properties especially the longitudinal polarizability, polarizability anisotropy, and first-order hyperpolarizability are significantly affected by the position of the methyl groups. The SHG and EOPE techniques can be potentially useful to discriminate the α, α -DMN isomers (2, 6-DMN < 2, 7-DMN < 2, 3-DMN) as well as the β, β -DMN isomers (1, 5-DMN < 1, 4-DMN < 1, 8-DMN). The (hyper)polarizability differences among the investigated DMNs were elucidated through density analysis calculations. The predicted polarizabilities exhibit good linear relationships with the experimental first-order biomass-normalized rate coefficient, a physicochemical property connected to the rates of biodegradation processes of polycyclic aromatic hydrocarbons.